Genomic Insights Into the Admixture History of Mongolic- and Tungusic-Speaking Populations From Southwestern East Asia - Chen, Jing; He, Guanglin; Ren, Zheng; Wang, Qiyan; Liu, Yubo; Zhang, Hongling; Yang, Meiqing; Zhang, Han; Ji, Jingyan; Zhao, Jing; Guo, Jianxin; Zhu, Kongyang; et al. (Frontiers in Genetics, 2021)
As a major part of the modern Trans-Eurasian or Altaic language family, most of the Mongolic and Tungusic languages were mainly spoken in northern China, Mongolia and southern Siberia, but some were also found in southern China. Previous genetic surveys only focused on the dissection of genetic structure of northern Altaic-speaking populations, however, the ancestral origin and genomic diversification of Mongolic and Tungusic-speaking populations from southwestern East Asia remain poorly understood due to the paucity of high-density sampling and genome-wide data. Here, we generated genome-wide data at nearly 700,000 single nucleotide polymorphisms (SNPs) in 26 Mongolians and 55 Manchus individuals collected from Guizhou province in southwest China. We applied principal component analysis (PCA), ADMIXTURE, f-statistics, qpWave/qpAdm analysis, qpGraph，TreeMix, Fst and ALDER to infer the fine-scale population genetic structure and admixture history. We found significant genetic differentiation between northern and southern Mongolic and Tungusic speakers, as one specific genetic cline of Manchus and Mongolians was identified in Guizhou province. Further results from ADMIXTURE and f-statistics showed that the studied Guizhou Mongolians and Manchus had a strong genetic affinity with southern East Asians, especially for inland southern East Asians. The qpAdm-based estimates of ancestry admixture proportion demonstrated that Guizhou Mongolians and Manchus people could be modeled as the admixtures of one northern ancestry related to northern Tungusic/Mongolic speakers or Yellow River farmers and one southern ancestry associated with Austronesian, Tai-Kadai and Austroasiatic speakers. The qpGraph-based phylogeny and Neighbor-joining tree further confirmed that Guizhou Manchus and Mongolians derived about half of the ancestry from their northern ancestors and the other half from southern indigenous East Asians. The estimated admixture time ranged from 600 to 1000 years ago, which further confirmed the admixture events were mediated via the Mongolians Empire expansion during the formation of the Yuan dynasty.